Kepuasan penumpang pada terminal bus di kawasan Pondok Cabe - Komarrudin, Achmad; Handayani, Susanty; Suryobuwono, Abdullah Ade; Ricardianto, Prasadja; Abdurachman, Edi (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, Indonesia, 2023)
The purpose of this research is to find out the influence of service quality, terminal accessibility toward passenger satisfaction, the influence of service quality, terminal accessibility and passenger satisfaction regarding passenger loyalty as well as indirect influence of service quality and terminal accessibility toward passenger loyalty concerning passenger satisfaction at Terminal Pondok Cabe. The samples for this research are 200 respondens who are passenger of Terminal Pondok Cabe. Data was collected using an online questionnaire, and analyzed using path analysis and the Sobel test. The research findings show that passenger loyalty is influenced by service quality and passenger satisfaction but not by terminal accessibility. Customer satisfaction can mediate the effect of service quality and terminal accessibility on customer loyalty.